Quality System Management in Medical Devices Industry in the Face of Normative Changes - Feliczek , Patryk (Studia Oeconomica Posnaniensia, 2016)
The medical devices industry covering wide range of products is significant for proper functioning of health assurance systems all over the world. Medical devices may be used in different conditions, both by individual users in homes and by specialized personnel in healthcare units. However, one must take into account that medical devices may be used by people who have already been sick, injured or have some other problem requiring healthcare service with the usage of medical devices. What is important is that the devices should be safe for its user and effective. It means that the devices should not have embedded unacceptable risk and they will work according to the specifications given by the label manufacturer. In order to assure such characteristics of medical devices, it is necessary to implement and maintain market law regulations, as well as normative requirements. That is why the main purpose of the article is to define and evaluate changes in quality management system for medical devices industry. The changes refer to law regulations in the European and Polish markets, as well as the normative area. ISO 13485 requirements were taken into consideration as a normative area.